Optimasi Formula Lipid Nanostruktur dengan Pentarget Manosa sebagai Sistem Penghantaran Rifampisin - Tri Suciati; Nurani Istiqomah; Benny Permana; Elin Julianti; Marlia Singgih Wibowo; Titah Yudistira; Yani Triyani (Fakultas Farmasi Universitas Pancasila, 2019)
Limited accumulation of anti-tuberculosis drugs in macrophages become a barrier to the success of latent tuberculosis therapy. The purpose of this study is to develop a D-mannose modified nanoparticle formula as a targeting agent to the mannose receptors to increase the internalization of rifampicin into macrophages. D-mannose was conjugated with chitosan using an amine reducing agent. Chitosan-D-mannose conjugate was characterized using FTIR. Subsequently, the conjugate was adsorbed onto the nanostructured lipid carrier (NLC) electrostatically. The NLC formula consisted of an ethyl acetate solution of solid-liquid lipid blend and rifampicin and an aqueous solution of chitosan-D-mannose conjugate, which were emulsified using polysorbate 80. Solidification of the NLC-chitosan-mannose nanoparticles was carried out by ionotropic gelation and solvent evaporation. The nanoparticle formula was optimized using Box-Behnken design. The formation of chitosan-D-mannose conjugate was shown by the change of the amide band wave number and the Schiff base formation of the FTIR spectra. The optimum formula of nanoparticles had a diameter of 766.1 ± 57.56 nm with a polydispersity index of 0.32 ± 0.02, encapsulation efficiency of 91.54 ± 0.18% and drug loading of 36.62 ± 0.07%. Rifampicin was released from the nanoparticles at pH 5.2 or 7.4 with a similar rate. This D-mannose modified NLC formula has the potential to be further developed as an intracellular antibiotic targeting to macrophages.